Security ethics - Hadjimatheou, Katerina; Guelke, John; Sorell, Tom (The library of essays on legal ethics and the enforcement of law, 2017)
Governments often act in the name of security to protect their citizenries. The essays in this volume seek to increase our understanding of state action in the name of security and take a range of viewpoints and approaches.